Correction of the spelling of Trichomycterus eichhorniarum Miranda Ribeiro, 1912 (Siluriformes: Trichomycteridae) - Koerber, Stefan; Azpelicueta, María De Las Mercedes (Zootaxa, 2014)
Miranda Ribeiro (1912) described Trichomycterus eichorniarum based on specimens caught between the pseudo-rhizomes of the water hyacinth Eichhornia azurea and named the species referring to this circumstance. In the description he missed an ‘h’ in both, the specific name and the provided reference to ‘Eichornea’. The latter is an orthographical variant of this generic name that should be “corrected to the validly published form of that name” according to Article 61.4 of the International Code of Nomenclature for Algae, Fungi, and Plants (Melbourne Code) (McNeill 2012).